Economics Valuation of Mangrove Forest in Supporting the Blue Economy and the Maqasid Al Sharia: A Case Study of Guraping Mangrove Forest, Sofifi, North Maluku - Misdiarso Wongsokarto; Achma Hendra Setiawan (Al-Iqtishad: Jurnal Ilmu Ekonomi Syariah, 2024)
This research aims to evaluate the economic value of the Guraping mangrove forest in Sofifi, Indonesia, and its alignment with blue economy principles and Maqasid al-Sharia objectives. This research uses a mixed-methods approach, combining quantitative and qualitative methods. Data were collected through surveys using questionnaires from 100 tourists, interviews with key informants, observations, and literature reviews. The results indicate that the economic value of Guraping Mangrove Forest support the concept of the blue economy and Maqasid al-Sharia. Guraping's mangrove forests positively contribute to the blue economy with direct and indirect use values. Besides, this economic valuation is also relevant in achieving Maqasid al-Sharia goals that emphasize the conservation of nature and sustainable socio-economic well-being.